The climate crisis is a water crisis - Nepal, Santosh (International Water Management Institute, 2024)
The climate crisis is marked by rapid changes that lead to more severe disasters, often resulting in irreversible impacts. Nepal faces this crisis, evident in rising temperatures, erratic rainfall patterns, and fast-melting glaciers. The climate crisis in Nepal is closely tied to an impending water crisis, affecting various sectors and communities across the country.